RESEARCH ON THE WELD FATIGUE STRENGTH OF FRAME BASED ON MULTI-AXIS THEORY - ZHANG MingYang; ZHANG KaiLin (Jixie qiangdu)
Taking two different structures of bogie frame as the research object, the multi-axis stress method was used to evaluate the side beam fillet weld fatigue according to DVS1612. The establishment means of the weld local coordinate system and the calculation method of material utilization are described in detail. It can be seen from the fatigue assessment results that the base plate fillet weld fatigue strength mainly depends on the normal stress parallel to weld; the vertical plate fillet weld fatigue strength is comprehensively affected by the stress in three directions, and the multi-axis effect is transparent. The material utilization of the vertical plate fillet weld is higher than the base plate, so the fatigue failure of side beam fillet weld first occurs at the vertical plate. The weld fatigue strength assessment relative dangerous areas of different frame structures are roughly identical, which verifies the accuracy and stability of the fatigue assessment method in this paper. This method provides a reference for the weld fatigue assessment of other equipment.